Locally Applied FK506 Improves Functional Recovery in Rats after Sciatic Nerve Transection - Goldani, Eduardo; Thomaz Monteiro Cardoso, Marco Antônio Smiderle Gelain,; Thaís Mariel Andara Beuren, Alice Cardoso Pellizzari, Mariana Dias Curra,; Oliveira Rangel, Juliana; Braga Silva, Jefferson (International Journal of Innovative Research in Medical Science, 2017)
Peripheral nerve injury (PNI) is a serious health concern for society and often causes long lasting disability. Nerve tubulization is recommended when there is too much tension for end-to-end coaptation and the gap between stumps is shorter than 3 cm. The immunosuppressive drug FK506 (Tacrolimus) has demonstrated neuroprotective and neurotrophic actions in experimental models by increasing neurite elongation and accelerating the rate of nerve regeneration in vitro and in vivo. The aim of this study was to evaluate functional recovery through walking track analysis after nerve transection with loss of substance. FK506 was used as a neurotrophic factor to stimulate neuronal growth through the tubulization technique along with a controlled drug delivery system, the alzet osmotic minipumps. Rats (n=36) were randomly assigned to three groups. Group I served as untreated controls. Groups II and III received 0.1 mg/kg/d of FK506 systemically and locally, respectively. After 90 days postoperative results showed the Group III achieved the best functional recovery (highest Sciatic Functional Index – SFI) in comparison with Groups I and II.